Determination of epms content and anti-inflammatory test rhizome extract Kaempferia galanga, L by inhibition of protein denaturation method - Laela Hayu Nurani; Aris Asahi; Hari Susanti (Universitas Ahmad Dahlan, 2020)
Kencur (Kempferia galanga, L) is one of the rhizomes that is often used as a constituent component in traditional medicinal formulas. One of the kencur's pharmacological activities is anti-inflammatory. The active compound as an anti-inflammatory is ethyl p-methoxycinnamate (EPMC). This study aims to determine the content and ascertainment of EPMC compounds and the anti-inflammatory activity of kencur rhizome extract. Kencur extract can be obtained by the maceration method using 96% ethanol solvent. The EPMC content determination was held using the TLC-densitometry method, while the EPMC compounds were confirmed using the GC MS method. The anti-inflammatory activity test was done using inhibiting protein denaturation methods. The extract results obtained 12.67% yield. The result of EPMC content in kencur extract was 10.05 ± 4.57. The GCMS kencur extract results showed an abundance of EPMC compounds at a retention time of 7.088 with a peak area of 72290779. The results of IC50 anti-inflammatory for the standard substance (EPMC) were 5.306 ± 5.028. The results of IC50 anti-inflammatory the sample (kencur extract) was 303.487 ± 1.201. Ethanol extract of kencur contains ethyl p-methoxycinnamate (EPMC) and has anti-inflammatory activity by inhibiting protein denaturation.